Analisis E-Service Quality Aplikasi DANA dalam Memenuhi Customer Satisfaction dengan Menggunakan Dimensi E-Servqual - Muhammad Zulfansyah Maulana Isnoe; Anton Mulyono Azis (LPPM Universitas Sains dan Teknologi Komputer, 2024)
DANA is one of the digital wallet service providersoperating in Indonesia since 2018. DANA isranked the third most frequently used digital wallet in Indonesia in 2022. This study aims to determine the effect of e-service quality on customer satisfaction in the DANA application by using the e-servqual dimension which consists of Efficiency, Fulfillment, Reliability, Privacy, Responsiveness, Compensation, and Contact, individually and also simultaneously on Customer Satisfaction of the DANA application. This research uses a quantitative approach that utilizes the survey method to collect data. This study uses an ordinal scale with a sample of 421 respondents with multiple linear regression methods and SPSS software, the results obtained partially the dimensions of Efficiency, Fulfillment, Privacy, Compensation, and Contact have a significant effect on customer satisfaction, while the dimensions of Reliability and Responsiveness do not have a significant effect. However, simultaneously the overall e-service quality has a significant influence on customer satisfaction of the DANA application.